Prevalence of Childhood Dermatological and Ocular Morbidities: A Cross-Sectional Study - Waseem Javed Mohammed; Gouhare Afshan; Amogh Harsoor; Anant Arunrao Takalkar; Ibrahim Siddiqui MD (Perspectives In Medical Research, 2024)
Introduction: Screening many children within a certain age group for the presence of illnesses can be efficiently conducted through school surveys. This study aims to analyze the prevalence of dermatological and ocular morbidities in school children. Methods: A school-based cross-sectional observational study was conducted in Government and Private schools of Latur, involving 500 school children aged between 5-14 years. Results: The prevalence of dermatological morbidities in our research was found to be 69%, with boys showing a prevalence of 50.6% and girls 18.4%. Prevalence of ocular morbidities was 7.6%, with boys showing a prevalence of 4.2% and girls 3.4%. Among dermatological manifestations, infections and infestations were the most observed (44%), followed by eczema (dermatitis) (13%). Refractive error was the most common ocular morbidity observed in boys (33.3%), followed by Vitamin A deficiency (28.57%). In girls, refractive error was the most common ocular morbidity (35.29%), followed by Vitamin A deficiency (29.41%). Conclusion: Urgent attention is needed to address these health issues early on to improve children's overall well-being. The findings contribute valuable insights for future research and targeted public health interventions aimed at promoting the health of school children.